A Flexible Aromatic Amphiphilic Trication for the Solubilization of Hydrophobic Organic Semiconductors in Water - Goudar, Soujanya H.; Kotha, Srinu; Pal, Manya; Ingle, Dhiraj S.; Rao, Kotagiri Venkata (Organic Materials, 2023)
Amphiphiles are widely explored for the solubilization of various hydrophobic molecules especially drugs in water. Recently, aromatic amphiphiles emerged as a new class of molecules for the solubilization of hydrophobic organic semiconductors in water. However, the synthesis of these systems involves several steps and often requires the use of expensive metal catalysts. Here we describe the design and synthesis of a new type of flexible aromatic amphiphilic trication (FAT) and its application for solubilization of hydrophobic organic semiconductors in water. FAT has been synthesized in two steps without the use of any expensive metal catalysts. We observed that FAT self-assembles in water into bilayer two-dimensional (2D) nanosheets composed of hydrophobic naphthalimide units. FAT is found to be effective for the solubilization of various hydrophobic organic semiconductors such as perylene, perylene diimide and C60 in water by encapsulating them into its hydrophobic domains. Moreover, FAT was also explored for the solubilization of a 2D conjugated ladder polymer, TQBQ (triquinoxalinylene and benzoquinone), in water.
Keywords: amphiphiles; host–guest chemistry; self-assembly; 2D nanosheets